Report of the Committee on Social Science Research - Planning Commission (Planning Commission, 1968)
The survey of the current situation in relation to research in these disciplines as mentioned in the first part of our terms of reference, if broadly interpreted, involves several dimensions. It could cover a countrywide survey of all institutions engaged in social science research-universities and colleges, research institutions and government departments. It could assess their present position, output growth, and examine the problems faced by them in organising and financing research activity and go into the division of responsibility and the extent of co-ordination between them.
Planning Commission Government of India
Planning Commission Government of India